Analysis And Estimation of The Efficiency of The Current State of Application of Drilling Fluids and Chemicals to Them - Urinov Sobir Nasilloyevich; Adizov Bobirjon Zamirovich (Zien Journals, 2022)
The article reflects the results of the analysis of the current state and assessment of the current efficiency of the use of drilling fluids when drilling vertical and horizontal wells in the conditions of productive horizons in the territory of the Republic of Uzbekistan. On the basis of the revealed results of the analytical study, recommendations are given for increasing the technological efficiency of the used drilling fluids and chemical additives to them.
Keywords: Well; drilling; drilling mud; chemicals